Instructional Design For The Teaching Of Speaking SkillAt SMP Muhammadiyah 10 Surakarta: A Naturalistic Study - Putri., Dini Fandriani; , Prof. Dr. Endang Fauziati, M.Hum; , Mauly Halwat H. Ph.D (2015)
This research aims at describing the instructional design for the teaching of speaking skill at SMP Muhammadiyah 10 Surakarta. It is conducted to know the implementation of the instructional design for the teaching speaking to the eight grade students in SMP Muhammadiyah 10 Surakarta.The researcher gets the data of this research from event, informant and document. The method of collecting data are observation in teaching speaking process and interview the teacher about the implementation of the instructional design of teaching speaking.The result of the analysis shows that the implementation of instructional design is as follows: 1) Learning objectives of teaching speaking are divided into two. The general objective is to develop the speaking skill of the learner communicative competence which includes the knowledge about how to use English appropriately in communicative situation. Then the specific objective is student can use English to make a simple transactional and interpersonal conversation to interact with their environment. 2) classroom procedure used by teacher is: first, engagement and explanation. Second, engagement, explanation and evaluation. Third, engagement, explanation, elaboration and explanation. Fourth, engagement, exploration, explanation, elaboration, and evaluation which is called 5E. 3) Classroom techniques used by teacher are as follows: question and answer, discussion, role playing, games, giving feedback, and summarizing. 4) The material used by the teacher was generally taken from some sources based on the syllabus. The teacher used textbook published by Kemdikbud as the printed material. The teacher also takes material from both printed and nonprinted source as access material on the internet or other resources such as picture. 5) The roles of teacher at SMP Muhammadiyah 10 Surakarta are facilitator, group organizer, motivator, and manager. 6) The roles of students at SMP Muhammadiyah 10 Surakarta are as active participant, member of group, learner's monitor and evaluate their own progress. 7) The media used by the teacher at SMP Muhammadiyah 10 Surakarta are: picture, audio, video and LCD. The teachers of SMP Muhammadiyah 10 Surakarta do not always use all the component of instructional design in teaching speaking especially in explorationcircle.